Comparison of 25-G Pencil Point Spinal Needle and 25-G Ballpen Spinal Needle in Spinal Anaesthesia - Çiçek, Müslüm; Köroğlu, Ahmet; Hasçalık, Mehmet; Ersoy, Mehmet Özcan (Fırat University, 2007)
Objectives: Tip design of spinal needle is one of the most important factors effecting the incidence of postspinal headache. We aimed to compare 25- G pencil point and 25-G ballpen spinal needles in terms of ease of usage, postspinal headache and backache rates.. Material and Methods: One hundred ASA I-II urologic surgery patients were randomized to Group P (Pencil point, 25-G Pencan needle) and Group B (Ballpen, 25-G Spinostar Ballpen needle). All patients received spinal anaesthesia in the sitting position. Perceptible click during the procedure and the identification time of cerebrospinal fluid after removal of the style were recorded. The anaesthetist evaluated the ease (easy, moderate, difficult, impossible) while patient evaluated the discomfort of the procedure using visual analogue scale. Postspinal headache and backache were recorded at 24 hours, 72 hours and 7 days postoperatively. Results: No statistical significance was observed among patient demographics, perceptible click rates, identification time of cerebrospinal fluid, anaesthetist evaluations, patient evaluations, postspinal headache (in group P no pain at 24 hours, 2% at 72 hours and 7 days; in group B 4.4% at 24 hours, 6.6% at 72 hours and 2.2% at 7 days) and backache (in group P 10.4% at 24 hours, 8.2% at 72 hours and 4.1%at 7 days; in group B 13.7% at 24 hours, 15.2% at 72 hours and 2.2% at 7 days). Conclusion: We propose that both spinal needles (25-G pencil point and 25-G ballpen) with diferent tip designs are similar in terms of ease of usage and postspinal headache and backache rates. ©2007, Firat University, Medical Faculty

Giriş: Spinal iğne ucunun dizaynı, spinal anestezi sonrası gelişen baş ağrısı sıklığını etkileyen en önemli faktörlerden biridir. Çalışmada 25-G pencil point ve 25-G ballpen spinal iğnelerini kullanım kolaylığı, spinal sonrası baş ve sırt ağrısı açısından karşılaştırmayı amaçladık.. Gereç ve Yöntem: ASA I-II 100 üroloji hastası rasgele Grup P (Pencil point) (25-G Pencan iğne) ve Grup B (Ballpen) (25-G Spinostar Ballpen iğne) olarak iki gruba ayrıldı. Bütün hastalara oturur pozisyonda spinal anestezi uygulandı. İşlem sırasında klik hissedilmesi ile stile çıkarıldıktan sonra beyin omurilik sıvısı görülmesine kadar geçen süre kaydedildi. Girişimi yapan anestezist işlemin kolaylığını (kolay, orta, güç ve imkansız), hasta ise işlemin rahatsızlığını Visual Analog Skala ile değerlendirdi. Spinal anestezi sonrası baş ve sırt ağrısı varlığı 24. ve 72. saat ile 7. günde sorgulandı. Bulgular: Hastaların demografik verileri, klik hissedilme oranı, beyin omurilik sıvısının görülme süresi, işlemin doktor ve hasta tarafından değerlendirilmesi, spinal sonrası baş ağrısı (grup P'de 24. saat'te ağrı görülmezken 72. saat ve 7. günde %2, grup B'de 24. saat'te %4.4, 72.saat'te %6.6 ve 7.günde %2.2) ve sırt ağrısı (grup P'de 24. saat'te %10.4, 72. saat'te %8.2 ve 7. günde %4.1, grup B'de 24. saat'te %13.0, 7. saat'te %15.2 ve 7. günde %2.2) açısından gruplar arasında anlamlı fark yoktu. Sonuç: Farklı uç yapılarına sahip 25-G pencil point ve 25-G ballpen spinal iğnelerinin kullanım kolaylığı, spinal sonrası baş ve sırt ağrısı açısından benzer oldukları kanaatine varıldı. ©2007, Fırat Üniversitesi, Tıp Fakültesi
Spinal Anestezide 25-G Pencil Point ve 25-G Ballpen Spinal İğnelerin Karşılaştırılması